Another Piece of Coffee - Lishan (et al.), Stuart (Cornfield Review, 2018)
group poem by: Victoria Bell Kylee Gill Lilly Grooms Stuart Lishan Candy Lucas Dani Miller Andrea Scheckelhoff Daniel Schirtzinger